Long-term effects of caesarean delivery on health and behavioural outcomes of the mother and child in Bangladesh - Mostafizur Rahman; Nuruzzaman Khan; Aminur Rahman; Mahmudul Alam; Alam Khan (BMC, 2022)
Abstract Background Medically unnecessary caesarean section (CS) is now an ongoing concern worldwide including in Bangladesh. This intensifies the occurrence of adverse maternal and child health outcomes. We investigated the associations of CS with some basic health and behavioural outcomes of the mothers and their children in Bangladesh. Methods We conducted a community-based case-control study from May to August 2019. A total of 600 mother-child dyads were interviewed using a structured questionnaire, 300 of them had CS, and 300 had vaginal delivery (VD) in their most recent live births. The exposure variable was the mode of delivery, classified as 1 if mothers had CS and 0 if mothers had VD. The outcome variables were a group of health and behavioural problems of the mothers and their children. Multivariate or multiple logistic regression model, separately for each health and behavioural outcome, was used to determine the effect of exposure variable on outcome variable after adjusting for possible confounders. Results The mean age and weight of mothers were 25.1 years and 53.1 kg, respectively. Likelihoods of headache, after delivery hip pain, problem of daily activities, and breastfeeding problem were reported higher among mothers who had CS in their most recent live birth than mothers who had VD. Similarly, children who were born through the CS operation were more likely to report breathing problem, frequent illness, lower food demand and lower hours of sleeping. Conclusion The use of CS increases the risks of health and behavioural problems of the mothers and their children. Policies and programs to avoid medically unnecessary CS and increase awareness over its adverse effects are important.